The Muslim Jesus : sayings and stories in Islamic literature - Khalidi, Tarif, 1938- (Cambridge, MA : Harvard University Press, 2001)
"This work presents in English translation the sayings and stories of Jesus in Arabic Islamic literature. In doing so, it traces a tradition of love and reverence for Jesus that has characterized Islamic though for more than a thousand years. A resource for the history of religions, the collection documents how one culture, that of Islam, assimilated the towering religious figure of another, that of Christianity." "Tarif Khalidi's introduction and commentaries place the sayings and stories in their historical context, showing how and why this "gospel" arose and the function it served within Muslim devotion. The Jesus that emerges here is a compelling figure of deep and life-giving spirituality. The sayings and stories, some 300 in number and arranged in chronological order, show us how the image of this Jesus evolved throughout a millennium of Islamic history."--Jacket
Introduction: The Muslim Gospel -- A Sketch of the Qur'anic Jesus -- Jesus in the Muslim Gospel -- The Early Context -- Emergence and Development -- The Earliest Sayings: Character and Function -- The Later Sayings and Stories -- The Sayings and Stories
Includes bibliographical references (pages 233-239) and indexes
Keywords: Jesus Christ -- Islamic interpretations; Jesus Christ -- In the Qurʼan; Islam -- Relations -- Christianity; Christianity and other religions -- Islam; Islamic stories; Islamic stories